Pathogenicity of Entomopathogenic Fungus Beauveria bassiana Against Leptocorisa acuta - Sari, Dian Ekawati; Kumalasari, Ade Sugiarti (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2022)
One of the main pests on rice plants difficult to control is Leptocorisa acuta. This pests has a distinctive odor and attacks rice plants in the generative phase. L. acuta attacks by sucking the rice grains at the milk stage so that the rice grains become empty and the quality reduced. High attack intensity will cause a decrease in rice production. The most widely used method in controlling these pests is the use of synthetic insecticides. The use of synthetic insecticides among farmers tends to be excessive so that cause damage the environment and other organisms. One of the controls that can replace synthetic insecticide and is environmentally friendly is the use of the entomopathogenic fungus Beauveria bassiana. The purpose of this study was to determine the pathogenicity of the fungus B. bassiana against L. acuta. The results showed that B. bassiana was able to cause mortality on L. acuta and its eggs ovicidal effects. Treatment of B. bassiana 60 g/L was able to cause mortality of L. acuta by 62.5% and unhatched eggs by 83.75 %.